(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
Battlefields have witnessed the appearance of a new generation of fighting methods, which relied on electronic technics and computers in managing different battles known as cyberwar. This war is considered among the threats on homeland security of countries. Its results are very big, due to its negative effects on different fields. That is for the sake of control and eliminate the country’s inferstructure. The aim of this study id to identify this cyberwar and its types, also we tackle some forms of cyber defense and protection.